Cryptosporidiosis outbreaks — United States, 2009–2017. Issue 9 (27th August 2019) - Gharpure, Radhika; Perez, Ariana; Miller, Allison D.; Wikswo, Mary E.; Silver, Rachel; Hlavsa, Michele C.
Abstract : This report describes the 444 cryptosporidiosis outbreaks that occurred in the United States between 2009 and 2017 and discusses preventive measures for this infection.